Redescriptions of three Milnesium Doyère, 1840 taxa (Tardigrada: Eutardigrada: Milnesiidae), including the nominal species for the genus - Michalczyk, Łukasz; Wełnicz, Weronika; Frohme, Marcus; Kaczmarek, Łukasz (Zootaxa, 2012)
In this paper we redescribe two species (Milnesium eurystomum Maucci, 1991 and Milnesium tardigradum Doyère, 1840) and one subspecies (Milnesium tardigradum granulatum Ramazzotti, 1962), which we elevate to the species level. We establish a new type series for M. tardigradum sensu stricto along with the sequences of the cytochrome c oxidase subunit I (COI) and the internal transcribed spacer 2 region (ITS2). Moreover, we define two species groups within the genus based on the appearance of the dorso-lateral cuticle (the tardigradum and the granulatum group, with smooth and reticulated cuticle, respectively) and propose a system for denotation of the number of points on secondary branches of claws in the genus. We also provide a diagnostic key to all described Milnesium species and discuss the world distribution of the genus.